PEMBERIAN AIR KELAPA MUDA DAN AIR CUCIAN BERAS PADA BIBIT KARET (Hevea brasiliensis) STUM MATA TIDUR - Purniawati, Dwi Indah; ', Sampurno; ', Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this study was to determine the best effect of giving interval coconut water and rice water dosage on the growth of rubber seeds sleeping eyes stum. The experiment was carried out in the greenhouse of Agriculture Faculty University of Riau, from February to May 2014. The study arranged experimentally using Completely Randomized Design(CRD) factorial two factor, factor I is an interval giving coconut water consists of 3 levels: 3 days, 6 days and 9 days. Factor II is rice water dosage consists of 3 levels: 0.75 l/plant, 1 l/plant and 1.25 l/plant and there are 9 combinations of treatments and treatments was repeated 3 times then obtained 27 experimental units, with each unit 3 seeds population. Parameters measured were the time of buds growth, trunk height, trunk diameter,number of leaves and leaf width. Data were analyzed statistically using ANOVA and followed by DNMRT at level of 5%. The results showed that the combination of intervals and coconut water 9 days and a dose of rice water 1,25 l/plant is the best result for trunk diameter, number of leaves and leaf width. Keywords: rubber seeds sleeping eyes stum, coconut water, rice water